High-temperature-resistant fireproof epoxy material for composite battery shell material
By using high-temperature fire-resistant epoxy materials for composite battery shell materials prepared with raw materials of specific ratios, the problems of high curing shrinkage, poor heat resistance and safety hazards of existing materials are solved, and the low curing shrinkage, heat resistance and fire resistance are improved, and the structural strength and service life of the battery shell are enhanced.
Patent Information
- Application Number
- CN202411736723.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
AI Technical Summary
The existing composite battery shell materials have high curing and shrinkage rates, high internal stress and defects in the appearance, resulting in low pass rate; poor heat resistance, which is easy to break and crack during transportation, handling, etc.; poor thermal conductivity, which leads to expansion and deformation of the battery due to high temperature when charging, and does not have fire-proof combustion performance, which poses a major safety hazard.
A composite battery shell material is made of high-temperature fire-resistant epoxy material, and is prepared by specific ratio raw materials (epoxy resin, diluent, flame retardant, polyamine, color paste and mold release agent), which improves the mechanical properties, processability and heat resistance of the material, meets the fire-resistant combustion performance of UL 94V0, and improves the interface bonding strength between the epoxy resin system and glass fiber cloth.
It achieves low curing shrinkage, improves the heat resistance and fire resistance of the material, avoids damage and expansion deformation of the battery case during transportation and charging, enhances structural strength and service life, and reduces safety hazards.
Smart Images

Figure CN119570197A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery shell materials, in particular to a high temperature resistant and fireproof epoxy material for a composite battery shell material. Background Art
[0002] The battery casing is an important part of the battery and is usually used to protect the chemical composition, battery cells and circuits inside the battery. It not only provides physical protection but also ensures the safe and stable operation of the battery. Depending on the different types of batteries, the material, design and function of the casing vary. Here are some key features and functions of the battery casing: The main function of the battery casing is to protect the electrolyte, active materials and battery cells inside the battery from external physical impact, corrosion, moisture and dust. This helps to extend the service life of the battery and maintain the stability of the battery.
[0003] The material of the battery casing needs to have certain strength, corrosion resistance, insulation and heat resistance. Common battery casing materials include:
[0004] Metal materials: such as aluminum, steel, stainless steel, etc. Metal casing provides good protection and heat dissipation performance, and is commonly found in lithium batteries, nickel-metal hydride batteries, lead-acid batteries, etc.
[0005] Plastic materials: such as polypropylene (PP), polystyrene (PS), etc. Plastic casings are relatively light and low cost, and are often used for small batteries, such as those in some portable devices.
[0006] Composite materials: sometimes reinforced materials or composite materials are also used. Composite materials have excellent chemical corrosion resistance, high and low temperature impact resistance, excellent mechanical properties, fireproof and insulation properties. They reduce weight while ensuring strength. Commonly used composite materials are mainly glass fiber reinforced resin-based composite materials, which have the characteristics of light weight, high strength, fatigue resistance, durability and good electrical insulation properties after molding.
[0007] Batteries generate heat during the charging and discharging process, especially high energy density batteries such as lithium batteries and lead-acid batteries. Therefore, the battery casing usually needs to have a certain heat dissipation capacity to prevent the battery from overheating and reduce the risk of thermal runaway or explosion. Metal casings often help to dissipate heat, and some plastic casings are also designed with heat dissipation holes or heat sinks.
[0008] The battery casing usually has electrical insulation to prevent the battery electrodes from contacting the external environment, avoiding dangers such as short circuits and leakage. The insulation layer is usually made of plastic or rubber materials, which can effectively prevent the battery electrodes inside the battery from contacting external metal objects, ensuring the safe use of the battery.
[0009] The existing composite battery shell materials use epoxy materials with high curing shrinkage, large internal stress in the product, and defects in appearance, resulting in low product qualification rate; poor heat resistance, during use, collisions due to transportation, handling, installation, etc., cause the shell to break and crack, especially in winter when the temperature is low, because the material is brittle and the impact performance decreases, the cracking is more obvious; when the battery is charging, heat is generated along with the transformation of internal activated substances. Because the shell has poor thermal conductivity and cannot dissipate heat in time, when it reaches or approaches the thermal deformation temperature of the material, it will cause the shell to expand and deform, especially in summer when the temperature is high, the expansion and deformation are more serious. In addition, conventional battery shell materials do not have fireproof and combustion performance, and there are major safety hazards. No solutions have been proposed for related technical issues. Summary of the invention
[0010] In view of the problems in the related art, the present invention proposes a high temperature resistant fireproof epoxy material for composite battery shell materials to overcome the above technical problems existing in the existing related art. The purpose of the present invention is to invent a battery shell material with good mechanical properties, processability and heat resistance, low curing shrinkage, UL 94V0 fireproof combustion performance, and high glass transition temperature. At the same time, the material also has good fluidity and wettability, improves the interface bonding strength between the epoxy resin system and the glass fiber cloth, and solves the problem of poor wettability and bonding between the conventional epoxy resin system and the glass fiber cloth.
[0011] To achieve the above object, the present invention provides the following technical solutions:
[0012] A high temperature resistant and fireproof epoxy material for a composite battery shell material is prepared from the following raw materials by weight percentage: 20-30% epoxy resin, 5-15% diluent, 35-45% flame retardant, 10-15% polyamine, 1-5% color paste and 1-2% release agent.
[0013] Preferably, the epoxy resin is one or more of bisphenol A epoxy resin and bisphenol F epoxy resin.
[0014] Preferably, the diluent is one or more of benzyl glycidyl ether, butyl glycidyl ether, and 1,4-butanediol diglycidyl ether.
[0015] Preferably, the flame retardant is brominated bisphenol A epoxy resin and brominated phenolic epoxy resin.
[0016] Preferably, the brominated bisphenol A type epoxy resin includes a high-brominated resin and a low-brominated resin, and the brominated novolac type epoxy resin is one or more of tetrabromobisphenol A, brominated novolac epoxy resin, and dibromopentaneerythroidal diglycidyl ether.
[0017] Preferably, the polyamine is one or more of dicyandiamide, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and polyethylenepolyamine.
[0018] Preferably, the color paste is one or more of oily color paste and resin color paste.
[0019] Preferably, the release agent is one or more of an internal release agent and an external release agent.
[0020] Preferably, the battery shell is prepared from the following raw materials in terms of weight percentage: 26% epoxy resin, 11% diluent, 45% flame retardant, 12% polyamine, 4% color paste and 2% release agent.
[0021] Preferably, the battery shell is prepared from the following raw materials in terms of weight percentage: 29% epoxy resin, 14% diluent, 37% flame retardant, 14% polyamine, 5% color paste and 1% release agent.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention is a high temperature resistant fireproof epoxy material for a composite battery shell material, which has good mechanical properties, processability and heat resistance, low curing shrinkage, meets UL 94V0 fireproof combustion performance, and has a high glass transition temperature, which effectively avoids damage and cracking of the battery shell due to factors such as transportation, handling, and installation during use; when the battery is charging, especially in summer, when the battery generates heat due to the conversion of internal activated substances, and the thermal conductivity and heat dissipation performance of the battery shell are poor, the power battery shell will not expand and deform due to high temperature;
[0024] (2) The present invention is a high temperature resistant and fireproof epoxy material for composite battery shell materials. The present invention has outstanding toughness and impact resistance, which greatly increases the structural strength of the power battery shell; when the temperature is low in winter, it effectively avoids the cracking of the power battery shell, greatly increases the impact performance of the power battery shell; reduces the brittleness of the battery shell, increases toughness, and improves bearing strength, which greatly increases the structural strength of the battery shell; when the battery generates high temperature due to charging and causes combustion, the flame retardant can decompose and absorb a large amount of heat from the combustion zone, so that the temperature of the combustion zone is reduced to below the critical combustion temperature, and the combustion is self-extinguished, thereby playing a flame retardant role on the battery shell. At the same time, the use of antioxidants can inhibit or delay the oxidation rate of the battery shell material, thereby extending the service life of the battery shell.
[0025] (3) The present invention is a high temperature resistant and fireproof epoxy material for composite battery shell material. The present invention has good fluidity and wettability, improves the interfacial bonding strength between the epoxy resin system and the glass fiber cloth, and solves the problem of poor wettability and bonding between the conventional epoxy resin system and the glass fiber cloth. It reduces the appearance defects and internal defects of the battery shell, such as high stress and low strength, and improves the mechanical strength and stability of the battery shell, extending the service life of the battery shell. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The viscosity change curve at different temperatures. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A high temperature resistant and fireproof epoxy material for a composite battery shell material is prepared from the following raw materials by weight percentage: 26% epoxy resin, 11% diluent, 45% flame retardant, 12% polyamine, 4% color paste and 2% release agent.
[0030] Furthermore, the epoxy resin is one or more of bisphenol A epoxy resin and bisphenol F epoxy resin.
[0031] Furthermore, the diluent is one or more of benzyl glycidyl ether, butyl glycidyl ether, and 1,4-butanediol diglycidyl ether.
[0032] Furthermore, the flame retardant is brominated bisphenol A epoxy resin and brominated phenolic epoxy resin.
[0033] Furthermore, the brominated bisphenol A type epoxy resin includes a high-brominated resin and a low-brominated resin, and the brominated novolac type epoxy resin is one or more of tetrabromobisphenol A, brominated novolac epoxy resin, and dibromopentaneerythroidal diglycidyl ether.
[0034] Furthermore, the polyamine is one or more of dicyandiamide, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and polyethylenepolyamine.
[0035] Furthermore, the color paste is one or more of oily color paste and resin color paste.
[0036] Furthermore, the release agent is one or more of an internal release agent and an external release agent.
[0037] Example 2
[0038] A high temperature resistant and fireproof epoxy material for a composite battery shell material is prepared from the following raw materials by weight percentage: 29% epoxy resin, 14% diluent, 37% flame retardant, 14% polyamine, 5% color paste and 1% release agent.
[0039] Furthermore, the epoxy resin is one or more of bisphenol A epoxy resin and bisphenol F epoxy resin.
[0040] Furthermore, the diluent is one or more of benzyl glycidyl ether, butyl glycidyl ether, and 1,4-butanediol diglycidyl ether.
[0041] Furthermore, the flame retardant is brominated bisphenol A epoxy resin and brominated phenolic epoxy resin.
[0042] Furthermore, the brominated bisphenol A type epoxy resin includes a high-brominated resin and a low-brominated resin, and the brominated novolac type epoxy resin is one or more of tetrabromobisphenol A, brominated novolac epoxy resin, and dibromopentaneerythroidal diglycidyl ether.
[0043] Furthermore, the polyamine is one or more of dicyandiamide, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and polyethylenepolyamine.
[0044] Furthermore, the color paste is one or more of oily color paste and resin color paste.
[0045] Furthermore, the release agent is one or more of an internal release agent and an external release agent.
[0046] Example 3
[0047] A high temperature resistant and fireproof epoxy material for a composite battery shell material is prepared from the following raw materials by weight percentage: 21% epoxy resin, 15% diluent, 45% flame retardant, 12% polyamine, 5% color paste and 2% release agent.
[0048] Furthermore, the epoxy resin is one or more of bisphenol A epoxy resin and bisphenol F epoxy resin.
[0049] Furthermore, the diluent is one or more of benzyl glycidyl ether, butyl glycidyl ether, and 1,4-butanediol diglycidyl ether.
[0050] Furthermore, the flame retardant is brominated bisphenol A epoxy resin and brominated phenolic epoxy resin.
[0051] Furthermore, the brominated bisphenol A type epoxy resin includes a high-brominated resin and a low-brominated resin, and the brominated novolac type epoxy resin is one or more of tetrabromobisphenol A, brominated novolac epoxy resin, and dibromopentaneerythroidal diglycidyl ether.
[0052] Furthermore, the polyamine is one or more of dicyandiamide, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and polyethylenepolyamine.
[0053] Furthermore, the color paste is one or more of oily color paste and resin color paste.
[0054] Furthermore, the release agent is one or more of an internal release agent and an external release agent.
[0055] The performance of the present invention is tested by standard samples at 23°C, as shown in Table 1 below.
[0056] project unit Typical Value Test Standards Tensile Strength MPa 55-65 ISO527 Bending Strength MPa 110-130 ISO178 Impact strength kJ / m2 12-30 ISO179 Flame retardant (1.5mm) / V-0 UL94
[0057] Table 1
[0058] The product should be stored in the original tightly sealed container in a dry environment at the storage temperature specified in the MSDS. Under these conditions, the storage period corresponds to the expiration date indicated on the packaging label. After this date, the product must be tested to determine whether it is still effective. If only part of the material in the container is used, it should be sealed immediately.
[0059] The gel time of the examples was tested, as shown in Table 2 below.
[0060] project unit value Gel time (80℃) s 150-200 Gel time (100℃) s 50-70 Gel time (110℃) s 35-45 Gel time (120℃) s 24-30 Gel time (130℃) s 15-20
[0061] Table 2
[0062] Note: The data shown are test results for pure resin / hardener systems. In composite structures, the gel times may differ from the given values depending on the fiber content and layer thickness.
[0063] The initial mixed viscosity of the embodiment at different temperatures was tested, as shown in Table 3 and Figure 1 .
[0064] project unit value Initial mixed viscosity (40℃) mPa.s 1700-2300 Initial mixed viscosity (80℃) mPa.s 220-260 Initial mixed viscosity (100℃) mPa.s 140-180 Initial mixed viscosity (120℃) mPa.s 100-130
[0065] Table 3
[0066] The operable time of the invention under the conditions of 100g, 65%RH and 23°C is 5-20min.
[0067] This medium temperature epoxy resin system is suitable for resin transfer molding (high pressure and low pressure) process and wet molding process.
[0068] High-pressure resin transfer molding, referred to as HP-RTM molding process, refers to the use of high pressure to mix resins and inject them into a vacuum-tight mold pre-laid with fiber-reinforced materials and pre-set inserts, and then obtain composite products through resin flow filling, impregnation, curing and demoulding.
[0069] The wet molding process is to lay cut carbon fiber or glass fiber dry cloth into a flat surface, transfer the material to the mold, apply glue to cover the fiber with resin, close the mold, evacuate, pressurize, heat and cure, open the mold, and take out the product.
[0070] The key to both processes is to set the right process conditions to control the curing reaction of the epoxy resin system. Some important parameters in the process include: mold temperature, pressure, and curing time. For the wet molding process, it is also necessary to control the thickness of the prepreg sheet, which is determined by the pressure and temperature applied during the production process. Typically, the thickness of the prepreg can be between 0.25 mm and 1 mm.
[0071] During the testing and production of this system, the following points should be noted:
[0072] (1) We recommend that each component be weighed using an accurate balance to avoid inaccurate mixing that affects the performance of the material system. Each component should be fully mixed to ensure uniformity.
[0073] (2) When processing a large amount of mixture, due to the exothermic reaction, the operating time will be shortened. It is recommended to divide the larger amount of mixture into several smaller containers.
[0074] (3) Release agent M7738 can be mixed as the third component or pre-mixed into 8573. The addition amount is 0.5-2%. The specific addition amount can be determined according to the demoulding behavior of the parts.
[0075] Mechanical and physical properties (guidance values)
[0076] Test system: Example
[0077] Curing process: 50℃*30min+120℃*20min
[0078] The standard sample was tested at 23°C and the results are shown in Table 4 below.
[0079]
[0080]
[0081] Table 4
[0082] Note 1:
[0083] Tg1: Sample curing process is 120℃*5min
[0084] Tg2: Sample curing process is 120℃*10min
[0085] Tg3: Sample curing process is 120℃*20min
[0086] Note 2: Shrinkage rate: The sample curing process is 120℃*5min; the test is carried out after constant temperature of 23℃*24h.
[0087] Note 3: Vertical combustion: GFRP thickness 1.5mm, 55% fiber volume content.
[0088] The present invention effectively avoids the battery shell from being damaged and cracked due to factors such as transportation, handling, and installation during use; when the battery is charging, especially in summer, when the battery generates heat as the internal activated substances are converted, and the thermal conductivity and heat dissipation performance of the battery shell are poor, the power battery shell will not expand and deform due to high temperature; the present invention has outstanding toughness and impact resistance, and greatly increases the structural strength of the power battery shell; in winter when the temperature is low, the cracking of the power battery shell is effectively avoided, and the impact performance of the power battery shell is greatly increased; the brittleness of the battery shell is reduced, the toughness is increased, the bearing strength is improved, and the structural strength of the battery shell is greatly increased; when the battery generates high temperature due to charging and causes combustion, the flame retardant can decompose and absorb a large amount of heat in the combustion zone, so that the temperature of the combustion zone is reduced to below the critical combustion temperature, and the combustion is self-extinguished, thereby playing a flame retardant role on the battery shell, and the use of the antioxidant can inhibit or delay the oxidation rate of the battery shell material, thereby extending the service life of the battery shell, having good mechanical properties, processability and heat resistance, low curing shrinkage, meeting UL 94V0 fireproof combustion performance, and high glass transition temperature. The invention solves the problem of poor wettability and bonding between conventional epoxy resin system and glass fiber cloth, improves the interface bonding strength between epoxy resin system and glass fiber cloth, improves the mechanical strength and stability of the battery shell, and prolongs the service life of the battery shell.
[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high temperature resistant and fireproof epoxy material for a composite battery shell material, characterized in that: The high temperature resistant and fireproof epoxy material for the composite battery shell material is prepared from the following raw materials by weight percentage: 20-30% epoxy resin, 5-15% diluent, 35-45% flame retardant, 10-15% polyamine, 1-5% color paste and 1-2% release agent.
2. The high temperature resistant and fireproof epoxy material for composite battery shell material according to claim 1, characterized in that: The epoxy resin is one or more of bisphenol A epoxy resin and bisphenol F epoxy resin.
3. The high temperature resistant and fireproof epoxy material for composite battery shell material according to claim 1, characterized in that: The diluent is one or more of benzyl glycidyl ether, butyl glycidyl ether, and 1,4-butanediol diglycidyl ether.
4. The high temperature resistant and fireproof epoxy material for composite battery shell material according to claim 1, characterized in that: The flame retardant is brominated bisphenol A type epoxy resin and brominated phenolic type epoxy resin.
5. The high temperature resistant and fireproof epoxy material for composite battery shell material according to claim 4, characterized in that: The brominated bisphenol A type epoxy resin includes a high-brominated resin and a low-brominated resin, and the brominated novolac type epoxy resin is one or more of tetrabromobisphenol A, brominated novolac epoxy resin, and dibromopentaneerythroidal diglycidyl ether.
6. The high temperature resistant and fireproof epoxy material for composite battery shell material according to claim 1, characterized in that: The polyamine is one or more of dicyandiamide, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and polyethylenepolyamine.
7. The high temperature resistant and fireproof epoxy material for composite battery shell material according to claim 1, characterized in that: The color paste is one or more of oily color paste and resin color paste.
8. The high temperature resistant and fireproof epoxy material for composite battery shell material according to claim 1, characterized in that: The release agent is one or more of an internal release agent and an external release agent.
9. The high temperature resistant and fireproof epoxy material for composite battery shell material according to claim 1, characterized in that: The battery shell is prepared from the following raw materials by weight percentage: 26% epoxy resin, 11% diluent, 45% flame retardant, 12% polyamine, 4% color paste and 2% release agent.
10. The high temperature resistant and fireproof cycloaliphatic material for composite battery shell material according to claim 1, characterized in that: The battery shell is prepared from the following raw materials by weight percentage: 29% epoxy resin, 14% diluent, 37% flame retardant, 14% polyamine, 5% color paste and 1% release agent.